Impact of Dynamically Changing Discharge on Hyporheic Exchange Processes Under Gaining and Losing Groundwater Conditions. Issue 12 (17th December 2018) - Wu, Liwen; Singh, Tanu; Gomez‐Velez, Jesus; Nützmann, Gunnar; Wörman, Anders; Krause, Stefan; Lewandowski, Jörg
Abstract: Channel discharge, geomorphological setting, and regional groundwater flow determine the spatiotemporal variability of bedform‐induced hyporheic exchange and the emergence of biogeochemical hot spots and hot moments that it drives. Of particular interest, and significantly understudied, is the role that dynamically changing discharge has on the hyporheic exchange process and how regional groundwater flow modulates the effects of transience. In this study, we use a reduced‐complexity model to systematically explore the bedform‐induced hyporheic responses to dynamically changing discharge events in systems with different bedform geometries exposed to varying degrees of groundwater flow (under both upwelling and downwelling conditions). With this in mind, we define metrics to quantify the effects of transience: spatial extent of the hyporheic zone, net hyporheic flux, mean residence time, and denitrification efficiency. We find that regional groundwater flow and geomorphological settings greatly modulate the temporal evolution of bedform‐induced hyporheic responses driven by a single‐peak discharge event. Effects of transience diminish with increasing groundwater upwelling or downwelling fluxes, decreasing bedform aspect ratios, and decreasing channel slopes. Additionally, we notice that increasing discharge intensities can reduce the modulating impacts of regional groundwater flow on the effects of transience but hardly overcomes the geomorphological controls. These findings highlight the necessities of evaluating hyporheic exchange processes in a more comprehensive framework. Key Points: Regional groundwater flow and geomorphological setting greatly modulate the impacts of dynamically changing discharge on hyporheic exchanges Effects of transience diminish with increasing groundwater gradients, decreasing bedform aspect ratios, and decreasing channel slopes Increasing flood intensities hardly overcomes the geomorphological controls on the effects of transience